The Relationship of Knowledge, Family Support, and Health Information Accessibility with Breast Self-Examination Motivation - Yuliatun, Laily; Saputriyana, Tasya; Masitah, Putri Dewi; Astari, Asti Melani; Fevriasanty, Fransiska Imavike (Indonesian Journal of Multidisciplinary Science, 2023)
Breast cancer is a malignancy that attacks the female breast. Based on data from the East Java Health Office for 2020, Sumenep Regency is the area with the most breast cancer and ranks 12th in East Java. One of the breast cancer screening efforts that can be done is the breast self-examination technique (BSE . This study aims to determine the relationship between the level of knowledge, family support and access to health information with the motivation to perform BSE in the Pagerungan Besar Islands, Sumenep Regency. This study uses a cross sectional design. The sampling technique used was consecutive sampling with a sample of 77 women. The research instrument used a questionnaire on the level of knowledge of family support, access to health information and BSE motivation. The i test used was the Spearman Correlation Test where a significant relationship was found between the level of knowledge and the motivation to perform BSE (p value=0.010; r=0.291), family support to the motivation to perform BSE (p value=0.00; r=) and relationship between access to health information and motivation to perform BSE (p value=0.005; r=). Increasing knowledge, family support and access to health information for women in the Pagerungan Besar Islands is very important to increase women's motivation to perform BSE as an effort to detect early breast cancer.